Determinant Of Burnout And The Implication Toward Job Satisfaction - Hidayat, Rahmat; Mardiyana, Mardiyana; Ronayah, Ronayah (Jurnal Manajemen Pelayanan Publik, 2024)
In government institutions, especially the service department, employee job satisfaction is very important since it will affect the service of government employees to people who need services. This research aims to determine the effect of workload and organizational climate on job satisfaction which is mediated by burnout. This research was carried out at the sub-district office in Bekasi district, with the objects being the employees who worked there. The research results show that workload and organizational climate partially influence burnout. Simultaneously, they both also influence burnout. The workload partially does not affect job satisfaction, while the organizational climate does. Burnout does not partially affect job satisfaction, but simultaneously with workload and organizational climate, it can influence job satisfaction. In this research, burnout only mediates workload on job satisfaction but does not mediate organizational climate on job satisfaction.